FOOD AVAILABILITY AND STATE SUPPORT FOR FOOD SECURITY DURING WAR - LOZYNSKA, Tamara (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The decrease in food availability as one of the indicators of food security in Europe has been noted since the beginning of the COVID-19 pandemic. The war in Ukraine caused a disruption in the supply chains of fertilizers, energy carriers and other resources needed by European and Ukrainian agricultural producers, which contributed to the increase in food prices. Thus, states as guarantors of food security must solve the task of ensuring the physical and economic availability of food products for the population. The purpose of the article is to highlight the dynamics of food availability in Ukraine and Europe, to identify the extent of the war’s impact on the population’s food supply, and to develop proposals for strengthening food security. In the research process, data from the Agroportal platform, the State Statistics Service of Ukraine, analytical reviews, research by domestic and foreign scientists, and the legal framework were used. In the research process, data from the Agroportal platform, the State Statistics Service of Ukraine, analytical reviews, research by domestic and foreign scientists, and the legal framework were used. A number of methods were used in the research process: comparison, index, generalization, formalization. A significant decrease in food availability was revealed both in Ukraine and in Europe as a whole. It has been established that the war in Ukraine caused a disruption in logistics, the removal of large tracts of land from agricultural use, an increase in the price of resources, and a complication in the export of food raw materials and its processing products. The main measures of the state policy to support food security are summarized, which differ in different countries, but have the same direction - elimination of social deprivation, protection of the poorest strata of the population, support of farmers’ incomes, reduction of obstacles in the way of movement of food products. Proposals have been developed to improve the physical and economic availability of food products. The war became a serious trigger for the transformation of not only food security policy, but also foreign trade, tax, price, protectionist and other policies related to the performance of social functions of the state. The multifaceted nature of the problem of food availability makes it necessary to carry out research in these and other areas.